2000
DOI: 10.1046/j.1365-2893.2000.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hepatitis C virus RNA and genotype from 6807 patients with chronic hepatitis C in the United States

Abstract: Hepatitis C virus (HCV) RNA status and HCV genotype have become important tools in the diagnosis and monitoring of therapy in chronic HCV infection. To establish a database with respect to HCV genotype and serum HCV RNA concentrations in chronic hepatitis C patients in the United States, we analysed 6807 chronic hepatitis C patients who had HCV RNA and HCV genotype tests conducted at a central laboratory. The HCV RNA concentration cut-off for the lower 25th percentile of this population (low titre) was 0.9 x 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
70
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(83 citation statements)
references
References 25 publications
10
70
0
3
Order By: Relevance
“…While the trak-C assay could not detect core antigen in 10 of 90 HCV RNApositive samples obtained from German hemodialysis centers (38), its Architect counterpart correctly recognized all of these specimens with very low levels of HCV viremia. Therefore, use of the Abbott test might provide at least an interim solution for the yet unresolved issue and the still ongoing discussion in the dialysis community of the need for and advantage of supplemental HCV RNA testing of anti-HCV-negative patients on maintenance hemodialysis (3,7,9,16,40). Similar considerations could apply to other settings, including transplantation medicine, in which the availability of a sensitive immunoassay for HCV core antigen determination should also represent a valuable diagnostic benefit for the immediate resolution of peculiar serological constellations which are particularly problematic in the course of decision making (20).…”
Section: Discussionmentioning
confidence: 99%
“…While the trak-C assay could not detect core antigen in 10 of 90 HCV RNApositive samples obtained from German hemodialysis centers (38), its Architect counterpart correctly recognized all of these specimens with very low levels of HCV viremia. Therefore, use of the Abbott test might provide at least an interim solution for the yet unresolved issue and the still ongoing discussion in the dialysis community of the need for and advantage of supplemental HCV RNA testing of anti-HCV-negative patients on maintenance hemodialysis (3,7,9,16,40). Similar considerations could apply to other settings, including transplantation medicine, in which the availability of a sensitive immunoassay for HCV core antigen determination should also represent a valuable diagnostic benefit for the immediate resolution of peculiar serological constellations which are particularly problematic in the course of decision making (20).…”
Section: Discussionmentioning
confidence: 99%
“…2 We found a lower prevalence of genotype 1 (62%) and a higher prevalence of genotypes 2 and 3 (38%) compared with a study of 6,807 patients from 10 clinic-based practices in the U.S., 73% and 22%, respectively. 24 Persons infected with HCV genotypes 2 and 3 have a higher success rate with antiviral treatments compared with those with genotype 1. 13,25 Thus, a higher proportion of ANs have a greater likelihood of responding to antiviral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In a large U.S. multicenter study, higher levels of HCV RNA also has been found in males compared with females and in persons infected with genotype 1 versus genotypes 2 and 3. 24 Male gender has been shown to be a risk factor for the development of fibrosis 8,28 ; the higher level of HCV RNA found in men could be a factor in this process, yet this remains to be proven.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic HCV is a leading cause of liver cirrhosis, end-stage liver disease, and hepatocellular carcinoma (2). Among the six known genotypes of HCV, the highly resistant genotype 1 is dominant (73-75%) in the USA (3,4). Treatment of chronic HCV infection includes weekly pegylated interferon alpha (PEGIFN) combined with weight-based ribavirin administered orally for up to 48 weeks (5).…”
Section: Introductionmentioning
confidence: 99%